Integration of Naqliyah in contemporary health discourse: a review - Mohamad, Hasbullah; Afandi, Aflah; Nik Hasmi, Nik Aizad; Zaini, Syahrir (Universiti Kebangsaan Malaysia (UKM), 2025)
Introduction: Naqliyah ( ةيلقنلا ), or Islamic revealed knowledge from the Qur’an and Hadith, offers profound guidance on well-being, including concepts like hifz al-nafs (preservation of life) and ethical conduct of healthcare professionals. Currently, the literature on the systematic integration of Naqliyah in contemporary health issues has not been reviewed. Our aim was to investigate the existing literature discussing various methods of integrating the naqliyah approach, with a focus on disease management and patient treatment within the healthcare system.